PEMANFAATAN TEPUNG BUAH LINDUR (Bruguiera gymnorrhiza) DALAM PEMBUATAN CRACKERS DENGAN PENAMBAHAN GLUTEN - Sarofa, Ulya; Yulistyani, Ratna; STP, Mardiyah (UPN VETERAN JAWA TIMUR, 2012)
Lindur flour is made from basic materials lindur fruit which has the advantage of the source of carbohydrate, high fiber, and mineral content. Making crackers with lindur fruit done proportion of lindur flour and wheat flour whereas added gluten.The Study aims to determine the effect of the proportion of wheat flour: wheat gluten fruit lindur to the physical, chemical and organoleptic lindur crackers. Research design used Completely Randomized Design comprised two factors, factor I is the proportion of wheat flour: flour lindur (70:30, 60:40, 50:50%) and factor II is the addition of gluten (10%, 12%, 14%). The results showed that the best treatment found in the proportion treated flour: flour lindur 70:30 (%) and the addition of 14% gluten, which produces fruit crackers lindur to yield 64.800%, 3.4483% water content, protein content of 9.7446 %, crude fiber content of 2.5224%, 17.1463 amylopectin content, the fracture (texture) 0.2805 (N/cm2) and organoleptic tests, including a sense of 3.95 / neutral, color 4.2 / like, the texture of 4 , and aroma 3/like 3.7 / neutral.keywords: Bruguiera gymnorrhiza, crackers, gluten